PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI PADA MATERI LEMBAGA KEUANGAN DALAM PEREKONOMIAN - Vitaloka Mawaddhah; Norida Canda Sakti (STKIP Persada Khatulistiwa Sintang, 2022)
This research is based on the low interest, involvement and attention of students when hybrid learning takes place. This research was carried out. So that the need for teaching media that is able to attract students' interest in learning. This development has the aim of seeing the feasibility, effectiveness, efficiency, along with student opinions and improving animated video props. This analysis utilizes the Research and Development scheme by going through 4 phases commonly known as 4-D. The subjects of analysis in this study were students from SMA Negeri 16 Surabaya class X IPS 1. The analysis was carried out by utilizing a Likert scale to validate the media, materials and items. The results of the analysis obtained from validation experts prove that the percentage of eligibility for teaching media, materials, effectiveness, and efficiency into groups is very feasible. Student responses obtained a percentage of 89.4% with a very feasible category to be used as teaching materials, especially when hybrid learning takes place and can be used in an effort to grow student ambition and passion for learning